Investigation on compressive characteristic of waste material geocomposite / Endy Raymond - Raymond, Endy (2007)
Waste materials have high potential to be recycled in civil engineering application. Many studies have been conducted local and abroad to explore the potential applications of waste material in civil engineering work. Among the applications are as backfill material for retaining wall, lightweight fill and many more. To maximize the recycling of waste material in Malaysia, the engineering properties of the waste material must first be known and characterized. This study therefore attempts to investigate the compressive characteristics of cement (OPC) bound waste material geocomposite. Two different waste materials namely scrap tire (waste material A) and waste plastic (waste material B) were investigated in this project. The specific gravity of waste material A and B were found to be 0.926 and 0.975 respectively. The minimum density of waste material A and B were found to be 0.366 g/cm3 and 0.423 g/cm3 respectively. A standard sample preparation and casting procedure for the OPC-waste material geocomposite was then developed in order to ensure the consistency of test result. Subsequently, three series of laboratory compression tests were conducted on the geocomposite involving repeatability testing, investigation on effect of exposure/curing condition and investigation on effect of OPC content. Repeatability testing on both Geocomposite A (OPC-Waste Material A) and Geocomposite B (OPC-Waste Material B) revealed high consistency with less than 3% difference was observed either in terms of geocomposite densities or compressive strength. The compressive stress of geocomposite A and B were found to decrease with severity of exposure condition. It is also observed that increasing OPC content would increase the compressive stress for both Geocomposite A and B. A comparison between Geocomposite A and B revealed that Geocomposite B can withstand higher compressive stress than Geocomposite A.